2017
DOI: 10.1016/j.fuproc.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative simulations and experiments for a novel yield model of coal devolatilization in oxy-coal combustion conditions

Abstract: Oxy-coal combustion is an emerging low-cost "clean coal" technology for emissions reduction and Carbon Capture and Sequestration (CCS). The use of Computational Fluid Dynamics (CFD) tools is crucial for the development of cost-effective oxy-fuel technologies and the minimization of environmental concerns at industrial scale. The coupling of detailed chemistry models and CFD simulations is still challenging, especially for large-scale plants, because of the high computational efforts required. The development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The posterior impact factor colored in green is significantly reduced via the verification and uncertainty quantification (V/UQ) approach, which uses the bound‐to‐bound approach to estimate the range of uncertainty of simulation and experimental data 45,74 . More details about this analysis are presented in publications of other group member 43,74 . Even V/UQ technique dramatically reduces the impact factor for most of the model parameters colored in green.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior impact factor colored in green is significantly reduced via the verification and uncertainty quantification (V/UQ) approach, which uses the bound‐to‐bound approach to estimate the range of uncertainty of simulation and experimental data 45,74 . More details about this analysis are presented in publications of other group member 43,74 . Even V/UQ technique dramatically reduces the impact factor for most of the model parameters colored in green.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum volatile yield is a function of the particle temperature and increases when increasing the particle temperature. Parameters in the ultimate volatile yield equation are fitted with the CPD model 43,44 …”
Section: Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, coal oxy-fuel combustion makes it possible to capture and sequester carbon, using technology already available in conventional pulverized coal boilers, and to capitalize on the enormous quantities of money invested in the existing boilers (Riaza et al, 2012). Some researchers (Sengupta and Basu, 1991;Stenseng et al, 1995;Iavarone et al, 2017;Gaikwad et al, 2017) focused their attentions on the development of mathematical models to predict coal combustion, gaseous emissions and combustion chambers performance. It was observed that biomass oxygen emissions are not extensively investigated and applications of oxyfuel combustion using cassava residues were not found.…”
Section: Features Gasification Combustionmentioning
confidence: 99%
“…Recently, Enderle et al [36] investigated the uncertainties arising from spray boundary conditions specifications in an ethanol flame using detailed chemistry. Despite uncertainties from the calibration of global chemistry models have been characterized in some studies ( [19][20][21]37]), their forward propagation through computational fluid dynamics (CFD) of combustion applications remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%